Evaluasi Dan Rancangan Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang BMK 35 Lori 4 PT. Bara Mitra Kencana. Kota Sawahlunto, Provinsi Sumatera Barat. - kurnia arrafi siregar; Rizto Salia Zakri (Journals Mining Engineering : Bina Tambang, 2021)
CV. Bara Mitra Kencana is a coal mining company located in Talawi District, Sawahlunto City, West Sumatra Province. The company has experienced an incident  fatality since January 2020 which occurred in the tunnel BMK35 lori 4. In order to prevent fatality in other tunnels, therefore it has  research mine ventilation system in the tunnel BMK35 lori 4. This study was conducted to obtain a likely factor causes of fatalityBased on KEPMEN ESDM Number 1827K / 2018 pages 104,107, and 177 regarding mine ventilation, the measurement results obtained are close to or not following details such as the air temperature at BMK35 Lori 4  from 29˚C to 31˚C, and humidity is between 95% to 100%. BMK35 Lori 4 has a concentration of oxygen (O2) 19.8%, Sulfide (H2S) 0%, Carbon Monoxide (CO) 0.036% and Methane (CH4) has been 0.35%. refer to the minimum air quantity requirement of 2,546 m3/s that have been fulfilled, so that the air needed in the field  by 2.4 m3/s.In order to overcome this problem, The researchers designed an underground mine ventilation system using the Ventsim software. The ventilation design was planned to use 3blowers with 16-inch diameter.. The blowers had used supplies  air to C6 and workface through a duct in a total of 2 pieces and  blower for exhaust air out of the mine mouth through ducts as much as 1 piece. The results of the simulation using the Ventsim application showed the air quantity increased from 2.4 m3/s to 2.7 m3/s.